The System Design Of Financial Literacy Strengthening And Taxation In Creative MSMEs Supports Sustainable Competitiveness - Reza Widhar Pahlevi; Adelia Rizky Safitri (Universitas Ahmad Dahlan, 2023)
Purpose-In order to determine whether the environment in the organization encourages Creative MSMEs to increase competitiveness through their level of financial and tax understanding, as well as encouraging organizations, this study aims to identify factors that affect the competitiveness of Creative MSMEs when viewed from that perspective. to establish a mechanism for enhancing taxation and financial literacy to boost long-term competitiveness that is then applied to Creative MSMEs. Design/Methodology/Approach-Participants in this study were from Special Region of Yogyakarta and Central Java's Creative MSMEs. To obtain its data, this study used convenient, intentional, and snowball sampling procedures, 15 MSMEs managers from various districts and the cities of Yogyakarta and Central Java served as informants for this study. Combining these techniques makes it simpler to select respondents and collect data from them who have been successfully operating Creative MSMEs for more than five years. After finding the responders, the snowball sampling technique was applied. Findings-The results show that having financial knowledge may be a great asset for MSME enterprises. The digital age expands market chains and boosts the creation of MSMEs, however owing to a lack of understanding of tax legislation, not all taxpayers, including MSMEs, can comprehend the necessary tax reporting implementation rules and processes. Additionally, MSMEs seem to be growing as a result of strategic initiatives to raise the human resource quality and growth of small and medium microentrepreneurs in Central Java and DI Yogyakarta. Research limitations/Implications-The limitations of a study are its flaws or shortcomings. Study limitations can exist due to constraints on research design, methodology, materials, etc., and these factors may impact the findings of your study. Originality/Value-This is your opportunity to provide readers with an analysis of the value of your results. It’s a good idea to ask colleagues whether your analysis is balanced and fair and again, it’s important not to exaggerate.